Irrigation, variety, and year exert a greater influence on organic potato production than microbial inoculation: case study results of a 2-year on-farm experiment - Papp, Orsolya; Kocsis, Tamás; Ganszky, Dániel; Hunyadi, Éva Borbélyné; Mezőfi, László; Labus, Balázs; Szigeti, Nora; Selmeczi, Dóra; Tóth, Ferenc; Darbon, Geoffrey; Drexler, Dóra (Frontiers in Sustainable Food Systems, 2025)
Potato holds significant importance in human nutrition. However, climatic stress factors such as prolonged drought have increasingly challenged potato production in recent years. Various research efforts are underway to mitigate the adverse effects of abiotic stress in potato agrotechnology, including the use of soil inoculation with beneficial microorganisms. Despite the promising results reported in the literature, there is still limited knowledge about the appropriate technology and microbial strains for field application, particularly in organic potato production. Therefore, a 2-year study was conducted to evaluate the effects of Pseudomonas brassicacearum 3Re2-7, Trichoderma asperelloides A, Rhizophagus irregularis MUCL41833, and Paraburkholderia phytofirmans PsJN strains under two irrigation strategies (irrigated and rainfed) in an organic potato field, using two varieties. Concerning the effects of microbial inoculations, significant differences were observed only in plant stomatal conductance among all measured parameters: inoculation with T. asperelloides significantly decreased stomatal conductance in potato plants. For the other studied parameters (yield, incidence of tuber pathogens, starch and phosphorus content of tubers, and SPAD values), the effects of variety, irrigation, and year were more significant than those of inoculation, regardless of whether strains were applied alone or in combination. The lack of significant inoculation effects may be attributed to open-field environmental conditions, limitations of soil nutrient status, application methodology, and resilience of the rich microbial communities associated with organic agriculture.